Gene Expression Profiling of Neospora caninum in Bovine Macrophages Reveals Differences Between Isolates Associated With Key Parasite Functions - García-Sánchez, Marta; Jiménez-Pelayo, Laura; Horcajo, Pilar; Regidor-Cerrillo, Javier; Collantes-Fernández, Esther; Ortega-Mora, Luis Miguel (Frontiers in Cellular and Infection Microbiology, 2019)
Intraspecific differences in biological traits between N. caninum isolates have been widely described and associated with variations in virulence. However, the molecular basis underlying these differences has been poorly studied. We demonstrated previously that Nc-Spain7 and Nc-Spain1H, high- and low-virulence isolates, respectively, show different invasion, proliferation and survival capabilities in boMØs, a key cell in the immune response against Neospora, and modulate the cell immune response in different ways. Here, we demonstrate that these differences are related to specific tachyzoite gene expression profiles. Specifically, the low-virulence Nc-Spain1H isolate showed enhanced expression of genes encoding for surface antigens and genes related to the bradyzoite stage. Among the primary up-regulated genes in Nc-Spain7, genes involved in parasite growth and redox homeostasis are particularly noteworthy because of their correlation with the enhanced proliferation and survival rates of Nc-Spain7 in boMØs relative to Nc-Spain1H. Genes potentially implicated in induction of proinflammatory immune responses were found to be up-regulated in the low-virulence isolate, whereas the high-virulence isolate showed enhanced expression of genes that may be involved in immune evasion. These results represent a further step in understanding the parasite effector molecules that may be associated to virulence and thus to disease traits as abortion and transmission